“MALLAPPESSANG OLOK-KOLOK”: PERJUMPAAN ISLAM DAN TRADISI LOKAL DALAM MEMORI KOLEKTIF MASYARAKAT BUGIS - Subair, Muh; Rusli, Rismawidiawati; Kila, Syahrir (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2023)
This article presents the findings of a qualitative research study that delves into the collective memory of the Bugis community concerning the intersection of Islam and local traditions. Collecting data through observation, interviews, and document analysis, this study shows that the Mallappessang olok-kolok (Releasing animals) tradition has sparked controversy in the community. The study analyzed the oral storytelling-based community’s tradition narratively. Mallappessang olok-kolok constitutes a “tolok bala” tradition, a local ritual designed for averting disasters. The Bugis society practices it by releasing animals into the forest to hope for healing from an illness. Some view the practice as contrary to Islam’s continuity from animism and dynamism and its implementation as unreasonable. On the other hand, others consider the tradition adheres to Islamic teachings. Releasing animals into the forest to feed wild animals expresses human harmony with nature. The act is also viewed as bonding with ancestors, following ancestral guidelines, and fostering community unity as families, relatives, and neighbors actively participate in the ritual. The narrative of this different perspective then rolls into a discussion or dialogue between Islam and local culture, which then impacts the existence of respect for the presence of these traditions. The conversation between Islam and local culture is a sign of progress in the thought of Islamic society that accepts traditions as heritage and science impacting on strengthening human relations with nature.